2017
DOI: 10.1111/ecca.12249
|View full text |Cite
|
Sign up to set email alerts
|

Mandated Political Representation and Redistribution

Abstract: Mandated political representation for minorities involves earmarking certain electoral districts where only minority‐group candidates are permitted to contest. This paper builds a political‐economy model to analyse the effect of such affirmative action on redistribution in equilibrium. The model predicts that in situations where the minority is economically disadvantaged and where voters exhibit an in‐group bias, such a quota can reduce transfers to poorer groups. This suggests that the gains to the minority g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For instance, Pande (2003) and Chin and Prakash (2011) provided supportive evidence in the case of India, where reservation has been in place for decades in favour of historically disadvantaged groups called the scheduled castes (SCs) and the scheduled tribes (STs). Other studies suggest that the effects may be heterogeneous within the minorities (Mitra 2018) or may not be persistent (Bhavnani 2017;Jensenius 2015). In the context of Kenya during the 1963-2011 period, Burgess et al (2015) found strong evidence of ethnic favouritism in road-building during periods of autocracy.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…For instance, Pande (2003) and Chin and Prakash (2011) provided supportive evidence in the case of India, where reservation has been in place for decades in favour of historically disadvantaged groups called the scheduled castes (SCs) and the scheduled tribes (STs). Other studies suggest that the effects may be heterogeneous within the minorities (Mitra 2018) or may not be persistent (Bhavnani 2017;Jensenius 2015). In the context of Kenya during the 1963-2011 period, Burgess et al (2015) found strong evidence of ethnic favouritism in road-building during periods of autocracy.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…10 In the present context, the seats themselves are reserved for SC and ST members, which decreases competition across groups, potentially leading to poorer overall quality. 11 There is a direct link between this idea and the theory developed in Mitra (2015), which shows that when the minority group is economically disadvantaged (as in the case of SCs and STs) and when voters favor candidates from their own group, political reservation actually reduces transfers to poor groups and can lead to an increase in inequality within minority groups.…”
Section: Potential Links Between Elected Minorities and Visits By Heamentioning
confidence: 99%
“…This is particularly important for the present study as the increase in welfare spending could come in the form of increased resources for doctors and medical workers, thus improving the quality of outcomes, while also encouraging a decline in absenteeism. 2 In contrast, some theoretical models have shown that in certain contexts, political reservation actually reduces transfers to poor groups (Mitra, 2015) or can create a sense of protection and security among health workers, which encourages further absenteeism. There is evidence that elected representatives have the ability to both improve outcomes for individuals (Iyer et al, 2012) and exasperate existing issues (Mishra, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these individuals have been prevented from reaching their full potential and further contributing productively to Indian society. Further, it is increasingly clear that this is not just an issue in India, but around the world, making research on both anti-discrimination and affirmative action policy essential (Mitra 2015).…”
Section: Approaches To Combating Discriminationmentioning
confidence: 99%
“…9,10 Although this paper details the case of India, it is further important to remember that political participation of minorities is an issue not just in India, but across the world. It is further increasingly concerning when minorities are socioeconomically disadvantaged (Mitra 2015).…”
Section: Approaches To Combating Discriminationmentioning
confidence: 99%